Oxidative stress in leukemia and antioxidant treatment. Issue 16 (20th August 2021) - Dong, Chao; Zhang, Nai-Jin; Zhang, Li-Jun
Abstract : Abstract: Oxidative stress is caused by the imbalance between the generation of free radicals/reactive oxygen species (ROS) and the antioxidant defense systems, which can activate various transcription factors and affect their transcriptional pathways. Oxidative stress plays an important role in the occurrence and development of leukemia and is closely related to the treatment and prognosis of leukemia. The standard chemotherapy strategies for the pre-treatment of leukemia have many drawbacks. Hence, the usage of antioxidants and oxidants in the treatment of leukemia is being explored and has been preliminarily applied. This article reviews the research progress of oxidative stress and leukemia. In addition, the application of antioxidants treatment in leukemia has been summarized.